Why do voters not always vote for warlords? A simple model of the free-riding problem in elections with violent candidates - Hansen, Bertel Teilfeldt (Politica, 2016)
In the literature on post-conflict elections it is commonly found that armed groups that obtain an insufficient number of votes often resume conflict. It is unclear, however, why this situation arises: Why do voters not always vote for threatening candidates and avoid conflict? The articles provides a theoretical answer to this question. In a one-shot game, voters choose between a civilian and a “warlord” who will engage in violence against them in inverse proportion to the number of votes he or she receives. The model shows that if voters individually obtain expressive utility from voting for the civilian, they will all end up doing so even if they prefer that the warlord is elected and violence is ended. In equilibrium, the maximum amount of violence occurs.